Ultraviolet aging of polyethylene microbeads and cadmium (Cd2+) uptake in water: surface morphology, kinetics, and isotherm analysis - Jumali, Saiful; Azman, Shamila; Mohamed Ibrahim, Mohd Johan; Sharipudin, Siti Shahidah (Universiti Teknologi MARA, Sarawak, 2026)
Polyethylene (PE) microbeads were subjected to three months of ultraviolet (UV) aging and evaluated for surface transformation and cadmium (Cd²⁺) uptake in aqueous solution. Scanning electron microscopy analysis showed that UV-aged microbeads developed pronounced surfaces, roughening with cracks and pit-like defects compared with virgin beads. This indicated an increased surface heterogeneity. Batch adsorption experiments (initial concentration, C0 = 0.2–1.0 mg L⁻¹) exhibited rapid Cd²⁺ uptake during the first few hours, followed by a slower approach to equilibrium at approximately 24–32 hours. Kinetic modelling showed that the pseudo-second-order (PSO) model better described the time-dependent data than the pseudo-first-order (PFO) model (coefficient of determination, R² ≈ 0.94–0.98 vs. 0.00–0.39), although model fits are treated as empirical descriptors rather than definitive evidence of a single adsorption mechanism. Equilibrium data were included using both Langmuir and Freundlich isotherms, which gave similarly good fits (R² = 0.95 and 0.96, respectively) within the tested concentration range; therefore, no conclusive preference for one isotherm was asserted. The Langmuir maximum adsorption capacity (qmax = 0.0060 mg g⁻¹) was extremely low, indicating that UV-aged PE microbeads are not suitable as engineered sorbents for water treatment. Instead, their environmental relevance is better interpreted as auxiliary sorbent phases and mobile vectors that may contribute to Cd²⁺ redistribution in aquatic systems. This study supports SDG 14 by demonstrating that UV aged PE microbeads can adsorb and transport Cd2+, underscoring their role in spreading pollutants and threatening aquatic ecosystem health.